STUDI KASUS: IBU HAMIL DENGAN NYERI PUNGGUNG: Case Study : Pregnant Women With Back Pain - Agustin Dwi Syalfina; Sari Priyanti; Dian Irawati (LPPM - STIKES Pemkab Jombang, 2022)
Back pain is a common symptom experienced during pregnancy. Even though the prevalence is high, this back pain complaint is not considered a serious problem in pregnancy even though it will have a bad impact on the quality of life of pregnant women if not properly managed. This study aims to determine the signs and symptoms and management of third trimester pregnant women with back pain. The type of research conducted is descriptive epidemiology case study type. The research subject Mrs.